Barriers to Differentiation: Applying Organizational Studies to Ontario Higher Education - Pizarro Milian, Roger; Davies, Scott; Zarifa, David (Canadian Journal of Higher Education, 2016)
Ontario’s Ministry of Training, Colleges and Universities is currently attempting to increase institutional differentiation within that province’s post-secondary education system. We contend that such policies aimed to trigger organizational change are likely to generate unanticipated responses. Using insights from the field of organizational studies, we anticipate four plausible responses from universities to the ministry’s directives: remaining sensitive to their market demand, ceremonial compliance, continued status seeking, and isomorphism. We provide several policy recommendations that might help the ministry overcome these possible barriers to further differentiation.